Communicative Action of Mothers of Kindergarten Children (Journal Of Educational and Psychological Researches, 2024)
The current research aims to investigate the communicative action of the mothers of Kindergarten children. It focuses on the problem of communicative action between the families of kindergarten children by verifying the objectives to identify the communicative action of these families. The population included the families of kindergarten children of the Baghdad (Karkh and Risafah) for the academic year 2022-2023. After preparing the communicative action rationality scale according to the standard steps of building up a scale and after submitting this scale to a committee of experts in the kindergarten field to show the validity and reliability, discrimination, and difficulty coefficient, the scale reached its final form with 18 items, 12 items concerning the social aspect, and 6 items concerning the moral aspect with the alternatives (I do it very often, I do it a lot, I do it sometimes, I do it rarely, I don't do it) in weighting (5, 4, 3, 2, 1). The scale was administered to a sample of 190 mothers that were chosen randomly. The results showed the existence of communicative action within the families of these children. According to that, the researchers presented some suggestions and recommendations.